From a Perceptual Point of View, Is There Prosodic Continuity Between Languages in Contact? - Roman-Montes de Oca, D (John Benjamins Publishing Company, 2019)
This paper contains the results of a set of perception tests that aimed at measuring perceived prosodic distances between different Romance languages (Italian, Friulian, Sardinian, Catalan, and Spanish). Data were collected within the framework of the AMPER project. The results were obtained by means of discrimination and identification tasks where the judges were 31 native speakers of Catalan form Barcelona and the stimuli were broad focus statements and yes-no questions in the above-mentioned languages. The perceived distances are then compared with the results of a dialectometric analysis of acoustic data. This comparison shows that the perceived distances are related to acoustic differences. © John Benjamins Publishing Company